Linking multi-scale 3D microstructure to potential enhanced natural gas recovery and subsurface CO2 storage for Bowland shale, UK. Issue 8 (29th June 2021) - Ma, Lin; Fauchille, Anne-Laure; Ansari, Humera; Chandler, Michael; Ashby, Paul; Taylor, Kevin; Pini, Ronny; Lee, Peter D.
Abstract : This paper quantitatively characterises the microstructure in shales across five scales in 3D, builds a multi-scale model of CH4 and CO2 flow pathways and storage, and assesses the potential of enhanced gas recovery and CO2 storage simultaneously. Abstract : Injection of CO2 into shale reservoirs to enhance gas recovery and simultaneously sequester greenhouse gases is a potential contributor towards the carbon-neutral target. It offers a low-carbon, low-cost, low-waste and large-scale solution during the energy transition period. A precondition to efficient gas storage and flow is a sound understanding of how the shale's micro-scale impacts on these phenomena. However, the heterogeneous and complex nature of shales limits the understanding of microstructure and pore systems, making feasibility analysis challenging. This study qualitatively and quantitatively investigates the Bowland shale microstructure in 3D at five length scales: artificial fractures at 10–100 μm scale, matrix fabric at 1–10 μm-scale, individual mineral grains and organic matter particles at 100 nm–1 μm scale, macropores and micro-cracks at 10–100 nm scale and organic matter and mineral pores at 1–10 nm-scale. For each feature, the volume fraction variations along the bedding normal orientation, the fractal dimensions and the degrees of anisotropy were analysed at all corresponding scales for a multi-scale heterogeneity analysis. The results are combined with other bulk laboratory measurements, including supercritical CO2 and CH4 adsorption at reservoir conditions, pressure-dependent permeability and nitrogen adsorption pore size distribution, to perform a comprehensive analysis on the storage space and flow pathways. A cross-scale pore size distribution, ranging from 2 nm to 3 μm, was calculated with quantified microstructure. The cumulative porosity is calculated to be 8%. The cumulative surface area is 17.6 m 2 g −1 . A model of CH4 and CO2 flow pathways and storage with quantified microstructure is presented and discussed. The feasibility of simultaneously enhanced gas recovery and subsurface CO2 storage in Bowland shale, the largest shale gas potential formation in the UK, was assessed based using multi-scale microstructure analysis. The potential is estimated to store 19.0–21.2 Gt CO2 as free molecules, together with 18.3–28.5 Gt CO2 adsorbed onto pore surfaces, implying a theoretical maximum of 47.5–49.5 Gt carbon storage in the current estimate of 38 trillion cubic metres (∼1300 trillion cubic feet) of Bowland shale. Simple estimates suggest 6.0–15.8 Gt CO2 may be stored in practice.